Pyrrolizine/indolizine-cinnamaldehyde Schiff bases: Design, synthesis, biological evaluation, ADME, and molecular docking study - Mohammed A.S. Abourehab; Alaa M. Alqahtani; Faisal A. Almalki; Ashraf N. Abdalla; Ahmed M. Gouda (Elsevier, 2022)
In the present study, two new Schiff bases 10a,b were synthesized by the condensation of 9a,b with cinnamaldehyde. The chemical structures of 10a,b were confirmed using spectral (IR, mass, 1H NMR, 13C NMR, and DEPT C135) and elemental analysis. The effect of 10a,b on the viability of five (SKOV-3, HeLa, HepG2, MCF-7, and SW620) cancer cell lines was evaluated, where MCF-7 ​cell line was the most sensitive. In addition, compounds 10a,b exhibited their cytotoxic activity against MCF-7 ​cells at IC50 values of 8.06 and 0.58 ​μM, respectively, compared to doxorubicin (IC50 ​= ​2.07 ​μM). Cell cycle analysis of MCF-7 ​cells treated with 10a revealed a significant increase (18 folds) of cell cycle at the pe-G1 phase, while 10b increased cell population at both pre-G1 and G2/M phase (11.5 and 2.5 folds increase, respectively). In addition, 10a induced 33 folds increase of combined early and late apoptotic cells, compared with 17 folds increase of combined apoptosis in MCF7 cells by 10b. Computational studies including target prediction, docking, and ADME studies were performed for 10a,b. The results revealed higher binding free energy for 10b toward COX-2 and p38 MAP kinase compared to 10a. To sum up, the results above suggested that 10b could be evaluated in future studies as a potential cytotoxic and apoptotic agent.